Visualization tools. - Adams, Annis Lee (Public Services Quarterly)
This article provides an overview and evaluation of several free and accessible data visualization and research tools useful for librarians, students, scholars, and professionals. It highlights Tableau Public, Datawrapper, Google Charts, Infogram, Flourish, mindmaps, and Litmaps, detailing their features, usability, and suitability for academic and professional contexts. Each tool is described in terms of ease of use, customization options, data privacy considerations, and potential applications such as storytelling with data, literature review support, or mind mapping. The article emphasizes the importance of selecting tools that align with users’ needs, including considerations of data sensitivity, interactivity, and collaboration, while noting limitations like mandatory public sharing on free plans. Overall, these platforms offer diverse options for enhancing data comprehension, presentation, and research workflows in educational and library settings.